Neonatal facial palsy without forceps use: report of two cases and review - Boussaadni, Yousra E. L.; Attaellah, Rabab; Oulmaati, Abdallah (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Neonatal facial palsy is a very rare diagnosis with only a few previously published cases of newborns, it can have varying etiologies apart from traumatic causes. The congenital, infectious, inflammatory, neoplastic causes must be eliminated before making the definitive diagnosis of traumatic facial paralysis. A multidisciplinary approach is recommended to differentiate various causes and initiate treatment in a timely manner. Corticosteroids have been used to minimize nerve damage and hasten recovery in the most of studies. We report in this work two cases at 2 and 3 days old of congenital unilateral facial palsy in newborns without history of obstetrical trauma with a good prognosis after corticosteroids with complete resolution.